PENGARUH VIRUS HEPATITIS C PADA RESPON CD4 SETELAH 6 BULAN PEMAKAIAN REGIMEN KOMBINASI ANTIRETROVIRUS LINI PERTAMA PADA PASIEN INFEKSI HIV - Somia, Agus; Utama, Susila; Parwati, Tuti; Wibawa, I Dewa Nyoman (journal of internal medicine, 2010)
Hepatitis C Viral (HCV) and Human ImmunodeÞ ciency Virus (HIV) infection are global health problems. Co-infectionHIV-HCV in intravenous drug users about 53 99%. Despite very high prevalence of this co-infection, there were controversiesabout impact of hepatitis C virus in CD4 response of HIV patients receiving anti retroviral therapy. We conduct a retrospectivecohort to Þ nd out the impact of hepatitis C virus in CD4 response after 6 months of Þ rst line ART therapy. We collect data fromVCT-CST clinic patient!s record. Inclusion criteria for this study were HIV patients more than 12 years old, receiving Þ rst lineof ART treatment, and with anti HCV result.Sixty two patients enrolled for this study. Twenty eight patients found positive anti HCV and 34 negative anti HCV result.Mean of age was 29 ± 4.44 years old in anti HCV (+) group and 34 ± 7.335 in anti HCV (-) group, male dominant (92.9% and85.3% respectively). There were no signiÞ cant differences in total lymphocyte count, hemoglobine, and transaminases (AST andALT) between the two groups. The increasing of mean CD4 after 6 months ART treatment higher in anti HCV (-) group than inanti HCV (+) group, but statistically not signiÞ cant.